(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This scientific article is devoted to the analysis of the problem of developing metalinguistic thinking in the process of parallel teaching of Russian and English from a psychological and pedagogical point of view. In the study, metalinguistic thinking is interpreted as the ability of a student to perceive two language systems not only at the level of practical speech, but also on the basis of conscious analysis, comparison and generalization. The article scientifically reveals the mechanisms of formation of metalinguistic consciousness in the conditions of parallel language teaching, its interrelation with cognitive development, language transfer and interference processes. The study, conducted on the basis of the IMRaD model, analyzes the possibilities of developing metalinguistic thinking through a comparative study of the phonetic, lexical and grammatical systems of Russian and English, and shows the limitations of traditional language teaching approaches. The results of the study substantiate the psychological and pedagogical conditions that contribute to the conscious perception of language systems by students in the process of parallel teaching, independent analysis of errors and effective assimilation of new language knowledge. The article proposes methodological approaches aimed at developing metalinguistic thinking in integrated teaching of Russian and English and provides scientific and practical recommendations for increasing the effectiveness of language education.